A sustainable manufacturing strategy decision framework in the context of multi-criteria decision-making - Ocampo, Lanndon A. (Animo Repository, 2015)
The present paper proposes a sustainable manufacturing strategy decision framework that integrates classical manufacturing strategy and sustainable manufacturing. Former approaches in these two fields were not inclusive; thus, an integrative decision framework is necessary. Along with this integration, the inclusion of major issues directly associated with manufacturing sustainability, such as firm size, various interests of different stakeholders and strategic responses, becomes a highlight of the proposed framework. Using an appropriate approach, the framework could provide the content of a sustainable manufacturing strategy which is helpful for manufacturing decision-makers in promoting both competitiveness and sustainability. Hypotheses are developed from the proposed framework. A review of a possible methodological approach is shown with a strong emphasis on multi-criteria decision-making. A discussion of a future work, following the decision framework, is also presented. The contribution of the present work lies in the development of a comprehensive decision framework that attempts to integrate a manufacturing strategy and a sustainable manufacturing. © 2015 Jordan Journal of Mechanical and Industrial Engineering. All rights reserved.